Guru PAI dan Moderasi Beragama di Sekolah - Zahra Rahmatika (TAFAHUS: JURNAL PENGKAJIAN ISLAM, 2022)
Religious moderation is built so that students have a neutral attitude, in the middle, not excessive and not extreme in viewing and behaving in religion. Seeing the current phenomenon, many generations find it easier to access various sources from social media platforms and so on, so that students easily waver in their beliefs and easily enter radicalism. Here the role of the Islamic Religious Education teacher here is indispensable in cultivating an attitude of religious moderation such as tawassuṫ (mengambil jalan tengah), tawāzun (harmony), i’tidāl (straight and firm), tasāmuḥ (tolerance), musāwah (egaliter), syūrā (discussion), iṣlāḥ (peace/reform), aulawiyyah (priority first), taṫawwur wa ibtikār (dynamic and innovative), dan tahaḍḍur (civilized). Therefore this study focuses on the discussion of the role of Islamic Religious Education teachers in building religious moderation in School.